Single‐fiber studies for assigning pathogenicity of eight mitochondrial DNA variants associated with mitochondrial diseases. Issue 8 (12th June 2020) - Zereg, Elamine; Chaussenot, Annabelle; Morel, Godelieve; Bannwarth, Sylvie; Sacconi, Sabrina; Soriani, Marie‐Hélène; Attarian, Shahram; Cano, Aline; Pouget, Jean; Bellance, Rémi; Tranchant, Christine; Lannes, Béatrice; et al.
Abstract: Whole mitochondrial DNA (mtDNA) sequencing is now systematically used in clinical laboratories to screen patients with a phenotype suggestive of mitochondrial disease. Next Generation Sequencing (NGS) has significantly increased the number of identified pathogenic mtDNA variants. Simultaneously, the number of variants of unknown significance (VUS) has increased even more, thus challenging their interpretation. Correct classification of the variants' pathogenicity is essential for optimal patient management, including treatment and genetic counseling. Here, we used single muscle fiber studies to characterize eight heteroplasmic mtDNA variants, among which were three novel variants. By applying the pathogenicity scoring system, we classified four variants as "definitely pathogenic" (m.590A>G, m.9166T>C, m.12293G>A, and m.15958A>T). Two variants remain "possibly pathogenic" (m.4327T>C and m.5672T>C) but should these be reported in a different family, they would be reclassified as "definitely pathogenic." We also illustrate the contribution of single‐fiber studies to the diagnostic approach in patients harboring pathogenic variants with low level heteroplasmy.